What empathizers do: empathy and the selection of everyday interpersonal emotion regulation strategies - Geiger, Eva J.; Prüßner, Luise; Barnow, Sven; Joormann, Jutta (Journal of affective disorders, 2025)
Background - Empathic behavior is crucial in promoting positive social outcomes and strengthening interpersonal bonds. Research on how empathy modulates responses to others' emotions remains scarce yet is fundamental for elucidating mechanisms of impaired social functioning in psychopathology and its treatment. - Methods - Two ecological momentary assessment studies (Ns = 125 and 204) investigated participants' empathy and usage of interpersonal emotion regulation strategies in 5537 social interactions. We measured empathy, a multi-faceted construct, as dissected into its components of mentalizing and experience sharing in Study 1, while Study 2 additionally investigated empathic concern and personal distress. - Results - Findings revealed that empathizers engage in significantly increased other-focused regulation, especially when feeling empathic concern. We also found differences in the strengths of the links between empathy and responses to others' emotions: When we mentalize, share others' emotions, or feel concerned, we choose more relationship-oriented strategies, including validation and soothing, and less cognitive reappraisal and avoidance to regulate others' emotions. In contrast, when personally distressed by others' emotions, we select more cognitive reappraisal and avoidance and less relationship-oriented strategies. - Limitations - Both studies relied on regulator reports. - Conclusions - Empathy facets distinctly shape our responses to others' emotions and can make us increasingly emotionally responsive and relationship-oriented. Understanding these dynamics can enhance the treatment of affective disorders characterized by deficits in social functioning.